Selecting Delivery Dates in the Tanker Scheduling Problem - Briskin, Lawrence E. (Management Science, 1966)
When scheduling tankers, it is necessary to determine delivery dates. If multi-port discharges are permitted it is also necessary to determine the proper volumes to be discharged at each port on a given voyage. This paper presents a means of determining a program of delivery dates and volumes for multi-port discharges which may be used in conjunction with an existing routing schema.